Pondok, Tsangaya, and Old Age Spiritual Wellbeing - Abubakar Yakubu (Tafkir: Interdisciplinary Journal of Islamic Education, 2021)
A Comparative analysis of practices obtained between the Pondok and Tsangaya with regard to traditional Islamic education and spirituality in Malaysia and Nigeria, indicates that, despite areas of similarity in origin and evolution, there exist a unique area of sharp contrast in relation to later life spirituality and elder care. The article maintains that, despite the two systems sharing wider similarities of originating from the traditional system of Arabic and Islamic education, the Pondok provides a complete platform for the spiritual life cycle, with opportunities for devotion from childhood to death. The Tsangaya on the other hand, covers childhood to early adulthood, thus, presenting a halfway approach to the spiritual life cycle. Recommendations were based on the need for the Tsangaya to model along aspects of the Pondok in a manner that will enable the incorporation of later life spiritual needs of the elderly. The purpose of this article is to carry out a comparative analysis of these two systems of traditional Islamic education , in relation to eldercare and spiritual wellbeing.  The relevance of this paper lies in the fact that population aging is currently receiving attention as global crises, and issues of elderly wellbeing in all aspects are being explored towards addressing the needs of the elderly.